Within the Bounds: The Role of Relocation on Intimate Partner Violence Help-Seeking for Immigrant and Native Women With Histories of Homelessness. (July 2016) - Crisafi, Denise N.; Jasinski, Jana L.
Our study examines the effects of abused women's relocation and recentness to an area on informal and formal help-seeking, and how access to personal and social resources affect these relationships. Secondary data analysis was conducted using a sample of 572 women with histories of abuse and homelessness who were interviewed at shelters in the state of Florida. Findings from nested linear regressions demonstrate that relocation affects formal help-seeking while recentness to an area affects informal help-seeking. Access to personal resources also predicts women's use of both informal and formal resources. Implications for intimate partner violence help-seeking are discussed.